Trust, Product Quality, and Consumer Loyalty of Scarlett Whitening Skincare - Mansyuri , M. Ikhwan; Mutmainnah; Iskandar , Rizkiana; Hayat, Nurul (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Consumer loyalty is a deep commitment to repurchase orsubscribe to a product or service consistently for the future, and does notaffect the existing environment or existing efforts or marketing effortscarried out, as well as other things that potential for the possibility ofconsumers switching to competing companies. This research wasconducted with the aim of finding out the influence of trust and productquality on consumer loyalty for Scarlet Whitening skincare in DompuRegency.Design/methodology/approach: This research is a quantitativedescriptive research with the analytical tool used in this research is SPSSV13. SPSS is statistical data processing software which functions toanalyze and manage statistics to make it easier for researchers to organize,interpret and process the data they obtain. The population in this studywere Scarlet Whitening skincare consumers in Dompu Regency who metthe research criteria, with a sample size of 42 respondents, on averagewomen aged 21-30 with high school education and income <500.000.Research Findings: The research results show that trust and productquality factors greatly influence consumer loyalty.Theoretical Contribution/Originality: Based on the available literature,the contribution to theory and originality regarding the influence of trust,product quality, and consumer loyalty of Scarlett Whitening Skincare canbe approached through the integration of customer relat